2006
DOI: 10.1002/ana.20889
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid load and cerebral atrophy in Alzheimer's disease: An 11C‐PIB positron emission tomography study

Abstract: To determine the relationship between cerebral amyloid plaque load and rates of cerebral atrophy in Alzheimer's disease. (11)C-PIB((11)C-6-OH benzothiazole)PET (positron emission tomography) findings were correlated with volumetric magnetic resonance imaging (MRI) measurements in nine subjects with mild to moderate AD. Analysis revealed a positive correlation between rates of whole brain atrophy and whole brain (p = 0.019) and regional (11)C-PIB uptake. This provides support for the central role of amyloid dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(103 citation statements)
references
References 18 publications
2
101
0
Order By: Relevance
“…Some studies have reported higher atrophy rates for AD subjects although subjects were often more severely affected at the time of imaging. For example, O'Brien et al reported a brain atrophy rate of 2.0%/year (0.9%/year) in patients with a mean age of 75 and mean MMSE of 16 [9]; Fox et al reported a brain atrophy rate of 2.4%/year (1.1%/year) for a mean age of 65 and mean MMSE of 20 [30]; Archer et al reported a brain atrophy rate of 1.8%/year (1.4%/year) for a mean age of 66 and mean MMSE 21 [31]; Wang et al reported a brain atrophy rate of 2.4%/year (1.2%/year) for a mean age of 67 and mean MMSE 20 [32]; Sluimer et al reported a rate of 1.9%/year (0.9%/year) for a mean age of 67 years and mean MMSE 22 [12]. The mean MMSE in ADNI is higher than the studies reported above, as ADNI enrolled at an early disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported higher atrophy rates for AD subjects although subjects were often more severely affected at the time of imaging. For example, O'Brien et al reported a brain atrophy rate of 2.0%/year (0.9%/year) in patients with a mean age of 75 and mean MMSE of 16 [9]; Fox et al reported a brain atrophy rate of 2.4%/year (1.1%/year) for a mean age of 65 and mean MMSE of 20 [30]; Archer et al reported a brain atrophy rate of 1.8%/year (1.4%/year) for a mean age of 66 and mean MMSE 21 [31]; Wang et al reported a brain atrophy rate of 2.4%/year (1.2%/year) for a mean age of 67 and mean MMSE 20 [32]; Sluimer et al reported a rate of 1.9%/year (0.9%/year) for a mean age of 67 years and mean MMSE 22 [12]. The mean MMSE in ADNI is higher than the studies reported above, as ADNI enrolled at an early disease stage.…”
Section: Discussionmentioning
confidence: 99%
“…Amyloid imaging with PiB retention and its relation to atrophy on MRI has been widely studied in Alzheimer's disease dementia (Archer et al, 2006;Jack et al, 2009;Chetelat et al, 2010), amnestic mild cognitive impairment and preclinical Alzheimer's disease (Andrews et al, 2013;Knopman et al, 2013;Petersen et al, 2013Petersen et al, , 2016Whitwell et al, 2013;Jack et al, 2014;Araque Caballero et al, 2015). Patients with probable DLB and Parkinson's disease dementia with high PiB retention have an Alzheimer's disease-like pattern of atrophy (Shimada et al, 2013) but longitudinal imaging studies investigating whether amyloid-b deposition influences rate of atrophy in patients with probable DLB are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…PIB also demonstrated the ability to discriminate between healthy young controls and older patients, with no significant retention seen in controls [6]. Subsequent studies were able to demonstrate congruence of findings, with retention of PIB and diagnosis consistent with AD [7][8][9][10] . Equivocal findings in patients with PIB retention and clinical diagnoses of MCI are variable likely owing to cofounders, including amnesia, depression, and alternative dementias playing a role.…”
Section: Compounds Of Interestmentioning
confidence: 83%